2008
DOI: 10.1051/0004-6361:20079203
|View full text |Cite
|
Sign up to set email alerts
|

Detection of amino acetonitrile in Sgr B2(N)

Abstract: Context. Amino acids are building blocks of proteins and therefore key ingredients for the origin of life. The simplest amino acid, glycine (NH 2 CH 2 COOH), has long been searched for in the interstellar medium but has not been unambiguously detected so far. At the same time, more and more complex molecules have been newly found toward the prolific Galactic center source Sagittarius B2. Aims. Since the search for glycine has turned out to be extremely difficult, we aimed at detecting a chemically related spec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
315
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 277 publications
(328 citation statements)
references
References 68 publications
12
315
1
Order By: Relevance
“…have value comparable to the present survey. SgrB2 appears as a noticeable exception, displaying significantly higher line densities, as high as 100 lines per GHz in the 3 mm range observed with IRAM (Belloche et al 2007) or 40 lines per GHz in the 1 mm range observed with SEST (Nummelin et al 1998(Nummelin et al , 2000. Interestingly, the slope of -0.9 that we observe for the cumulative number of lines versus flux threshold is identical to the slopes observed by Schilke et al (2001), White et al (2003), and Comito et al (2005) in their submillimeter surveys of Orion-KL.…”
Section: Comparison With Previous Surveysmentioning
confidence: 80%
See 1 more Smart Citation
“…have value comparable to the present survey. SgrB2 appears as a noticeable exception, displaying significantly higher line densities, as high as 100 lines per GHz in the 3 mm range observed with IRAM (Belloche et al 2007) or 40 lines per GHz in the 1 mm range observed with SEST (Nummelin et al 1998(Nummelin et al , 2000. Interestingly, the slope of -0.9 that we observe for the cumulative number of lines versus flux threshold is identical to the slopes observed by Schilke et al (2001), White et al (2003), and Comito et al (2005) in their submillimeter surveys of Orion-KL.…”
Section: Comparison With Previous Surveysmentioning
confidence: 80%
“…They have covered the whole range of frequencies reachable from the ground, from the 3 mm range observed with IRAM, SEST, NRAO, or JCMT to the submillimeter windows observable with the CSO and JCMT (MacDonald et al 1996;Schilke et al 1997;Helmich & van Dishoeck 1997;Nummelin et al 1998;Thompson & MacDonald 1999;Kim et al 2000;Nummelin et al 2000;Lee et al 2001;Schilke et al 2001;White et al 2003;Comito et al 2005;Kim et al 2006;Belloche et al 2007;Olofsson et al 2007;Tercero et al 2010). The line densities usually range from 10 to 20 lines per GHz, i.e.…”
Section: Comparison With Previous Surveysmentioning
confidence: 99%
“…In addition that in the case of our dataset, the last parameters vary from one datacube to the next, so that η D is only an average value. It is, however, a first indication of the relative importance of the confusion problem -a similar indicator was given by Belloche et al (2008) for their search and detection of amino acetonitrile in Sgr B2(N).…”
Section: Fraction Of Blended and Detected Linesmentioning
confidence: 83%
“…1,61 The exact origin of these species is still unclear, but recent models indicate that surface reaction mechanisms are most likely the main formation channel. 2 Garrod 2 showed that the gas-phase formation of glycine (NH 2 CH 2 COOH) in hot cores depends on the timescale of the hot-core evolution and the availability of precursor species in the gas phase.…”
Section: Astrophysical Implicationsmentioning
confidence: 99%